1999
DOI: 10.1002/(sici)1097-0134(19990815)36:3<318::aid-prot6>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for protein-ligand binding studies: Application to a model for drug resistance, the HIV/FIV protease system

Abstract: A protocol for the rapid energetic analysis of protein-ligand complexes has been developed. This protocol involves the generation of protein-ligand complex ensembles followed by an analysis of the binding free energy components. We apply this methodology toward understanding the origin of binding specificity within the human immunodeficiency virus/feline immunodeficiency virus (HIV/ FIV) protease system, a model system for drug resistance studies. A distinct difference in the internal strain of an inhibitor wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…Modeling indicated that the I35 30 D substitution, which is located within the S2 and S2Ј subsites, might be the major determinant for the P2 and P2Ј preference. The FIV I35/HIV-1 D30 residue has been implicated as being involved in defining the binding specificity between FIV and HIV-1 PRs in a protein-ligand study (6). I35 30 D is the only substitution inside the substrate-binding pocket that failed to be engineered successfully into FIV PR and generate active enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Modeling indicated that the I35 30 D substitution, which is located within the S2 and S2Ј subsites, might be the major determinant for the P2 and P2Ј preference. The FIV I35/HIV-1 D30 residue has been implicated as being involved in defining the binding specificity between FIV and HIV-1 PRs in a protein-ligand study (6). I35 30 D is the only substitution inside the substrate-binding pocket that failed to be engineered successfully into FIV PR and generate active enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…The significant increase in activity of mutants I37V and Q99V against the HIV-1 junction and phage library peptides suggested that FIV protease has smaller S1/S2/S3 substrate-binding pockets than HIV-1 protease. It has been suggested that crowding within the active site is responsible for the increased specificity of FIV protease (4). The P2/NC and RT/IN junction peptides are the most efficiently cleaved by HIV protease among all the HIV-1 Gag and Gag-Pol cleavage junction sites.…”
Section: Discussionmentioning
confidence: 99%
“…Using a molecular dynamics/simulated annealing protocol, Dominy and Brooks [24] evaluated various energy components, including the interaction energy between the ligand and each protein environment, internal energy differences between the bound ligand in each protein environment, electrostatic solvation free energy change on binding, and hydrophobic solvation free energy change on binding of the LP149 inhibitor. Using a molecular dynamics/simulated annealing protocol, Dominy and Brooks [24] evaluated various energy components, including the interaction energy between the ligand and each protein environment, internal energy differences between the bound ligand in each protein environment, electrostatic solvation free energy change on binding, and hydrophobic solvation free energy change on binding of the LP149 inhibitor.…”
Section: Hiv-proteasementioning
confidence: 99%